Ethnography and education policy - Walford, Geoffrey (Amsterdam : JAI, 2001)
This book emphasises the central place that ethnographic work should have in the formulation and evaluation of education policy. Ethnographic studies contribute to a greater understanding of the process formulation, evaluation and critique. First, careful studies of policy initiatives at the local level can show the extent to which change actually occurs in practice. Second, ethnographic studies can investigate the unintended consequences as well as those planned by the policy. Third, ethnography can investigate the effects of policies in such a way that contradictions within the original policy itself are illuminated. As well as studying the effects and impact of policy, ethnography can also be useful in the formulation of new policies. The various chapters gathered together here give many examples of the ways that ethnography can trace the effects of particular policy developments and may be able to influence future policy debates. The contributors and case studies relate to several countries including the United States, Italy, England, France, Sweden and Switzerland, showing not only that ethnographic research in education is now widespread, but also increasing relevance to policy.
Includes bibliographical references.
Description based on print version record.
Keywords: Education and state; Ethnology; Education -- Political aspects; Physical anthropology & ethnography; Organization & management of education; Education -- General